Assessment of groundwater quality in Khulna city of Bangladesh in terms of water quality index for drinking purpose - Asif Mahmud (Applied Water Science, 2020)
Abstract Valuation of water quality index (WQI) is one of the simplest, easily understandable, and efficacious techniques to evaluate the quality and suitability of water for drinking as well as other purposes. This research was aimed to investigate the drinking water quality of tube wells from different areas in Khulna City, Bangladesh, by developing the WQI. Water samples from 59 tube wells were collected from different locations during the pre-monsoon time. pH, electric conductivity (EC), dissolve oxygen (DO), total dissolved solid (TDS), chloride (Cl−), nitrate (NO3 −), and total hardness of the collected water samples were analyzed for the calculation of WQI. The mean value for pH, EC, DO, TDS, Cl−1, NO3 −, and total hardness was 7.30, 1650 μS/cm, 1.60 mg/l, 1188.7 mg/l, 414.6 mg/l, 0.029 mg/l, and 52.03 mg/l, respectively. The calculated WQI values for individual places were distributed spatially through mapping by using ArcGIS software. Based on the WQI values, the drinking water was categorized into excellent, good, poor, very poor, and unfit for drinking purposes. The calculated WQI values ranged from 40.11 to 454.37 with an average value of 108.94. Among all the groundwater samples, 11.86% were excellent, 54.24% were good, 23.73% were poor, 1.69% were very poor, and 8.47% were unfit for drinking purpose based on WQI. The results showed that the groundwater quality of most of the studied areas of Khulna city could be considered safe and suitable for drinking barring the elevated EC and chloride content in some areas. Since Khulna city is situated in the southwestern part of Bangladesh and gradually approaches toward the base level of the Bay of Bengal which might be the source of salt concentration in the groundwater of Khulna city, Bangladesh.